Programa Brasil sem homofobia: uma análise acerca das repercussões do programa no Maranhão - FREITAS, Luciane Fontinele de (2024)
The "Brasil Sem Homofobia (PBSH)" program, started in 2004, is a wide scale approach on how to deal with the demands of the LGBT+ population in Brazil, attempting to guide both the public government sectors and civil society towards another attitude regarding LGBTphobia. This study has the objective of analyzing the strategies of implementing BSG since its inception, while trying to understand the context of its creation and its possible repercussions. To guide this bibliographical research, we needed to contextualize the program's creation, much like the narratives associated with it and the consequences of the local project "Escola Sem LGBTfobia" on the state of Maranhão in Brazil. School was thought as a viable space for the development of such a project because it is a space where several different forms of oppression related to gender and sexuality appear. We establish the context of the implementation of PBSH in 2004, followed by a bibliographic survey of articles and other scientific writings that discussed the program after its creation. Finally, we analyze the "Escola Sem LGBTfobia" project as a descendant of PBSH, while trying to understand the factors involved in the execution of such a project in the state of Maranhão. Despite the challenges faced after its implementation, such as resistance from opposing parties, disinformation and cultural prejudice, PBSH still has effects, sowing seeds all around the nation. This study highlights the importance of programs like PBSH for promoting equality and fighting discrimination based on sexual orientation and gender identity. Such research is pertinent to the "Programa de Pós- Graduação em Psicologia", especially its approach regarding History, Epistemology and Psychosocial Phenomena. We conclude, therefore, that the success of programs like PBSH depends on a transformation through Education in order to achieve the full functioning of such actions and that the failures of the program were a direct consequence of institutionalized LGBTphobia in the country.